Overexpression of Galectin 3 in Pancreatic β Cells Amplifies β-Cell Apoptosis and Islet Inflammation in Type-2 Diabetes in Mice - Petrovic, Ivica; Pejnovic, Nada; Ljujic, Biljana; Pavlovic, Sladjana; Miletic Kovacevic, Marina; Jeftic, Ilija; Djukic, Aleksandar; Draginic, Nevena; Andjic, Marijana; Arsenijevic, Nebojsa; Lukic, Miodrag L.; Jovicic, Nemanja (Frontiers in Endocrinology, 2020)
Aims/Hypothesis: Galectin 3 appears to play a proinflammatory role in several inflammatory and autoimmune diseases. Also, there is evidence that galectin 3 plays a role in both type-1 and type-2 diabetes. During obesity, hematopoietic cell-derived galectin 3 induces insulin resistance. While the role of galectin 3 expressed in islet-invading immune cells in both type-1 and type-2 diabetes has been studied, the importance of the expression of this molecule on the target pancreatic β cells has not been defined. Methods: To clarify the role of galectin 3 expression in β cells during obesity-induced diabetogenesis, we developed transgenic mice selectively overexpressing galectin 3 in β cells and tested their susceptibility to obesity-induced type-2 diabetes. Obesity was induced with a 16-week high-fat diet regime. Pancreatic β cells were tested for susceptibility to apoptosis induced by non-esterified fatty acids and cytokines as well as parameters of oxidative stress. Results: Our results demonstrated that overexpression of galectin 3 increases β-cell apoptosis in HFD conditions and increases the percentage of proinflammatory F4/80+ macrophages in islets that express galectin 3 and TLR4. In isolated islets, we have shown that galectin 3 overexpression increases cytokine and palmitate-triggered β-cell apoptosis and also increases NO2−-induced oxidative stress of β cells. Also, in pancreatic lymph nodes, macrophages were shifted toward a proinflammatory TNF-α-producing phenotype. Conclusions/Interpretation: By complementary in vivo and in vitro approaches, we have shown that galectin 3-overexpression facilitates β-cell damage, enhances cytokine and palmitate-triggered β-cell apoptosis, and increases NO2−-induced oxidative stress in β cells. Further, the results suggest that increased expression of galectin 3 in the pancreatic β cells affects the metabolism of glucose and glycoregulation in mice on a high-fat diet, affecting both fasting glycemic values and glycemia after glucose loading.